The Emergence of a Muslim Minority in the Ado-Ekiti Kingdom of Southwestern Nigeria (American Journal of Islam and Society, 2013)
This paper seeks to provide a sociological reinterpretation ofIslam’s presence in the Ado-Ekiti kingdom by unraveling the variousessentially sociopolitical and economic factors that, alongwith religious factors, account for its emergence and growth. Ihave adopted a historical methodology (narrative) to understandand explain its appearance, functions, and contributions in thekingdom. This will be supplemented with material found in publicand private libraries, archives and museums, and artifacts.The paper reveals that the exact date of Islam’s introduction remainsunknown and that local Muslims worshipped in secret until1836, when a Muslim named Ali Atewogboye ascended thethrone. He and his successor gave Islam a strong foundation dueto their sociopolitical and economic motivations. The paper closeswith an account of the factors that facilitated Islam’s spread, theproblems faced by local Muslims, and how they have tried to resolvethese problems.